Connecting film, conductive composite and photovoltaic module
By setting areas with different pre-crosslinking degrees on the connecting film and setting the conductive part in the high pre-crosslinking degrees area, combined with irradiation processing technology, the problem of dummy welding caused by excessive fluidity of the connecting film is solved, and the power generation efficiency and connection reliability of the photovoltaic module are improved.
Patent Information
- Application Number
- CN202210473503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-04-29
AI Technical Summary
The connecting membranes in existing main gateless photovoltaic modules have too much fluidity, causing the membrane material to penetrate between the conductor and the fine gate lines, causing dummy welding, affecting power generation efficiency, and the multi-layer film structure processing technology requirements are high, and stress is prone to occur to cause membrane separation.
By setting a first region with low pre-crosslinking degree and a second region with high pre-crosslinking degree on the connecting film, the conductive portion is arranged on the surface of the second region and pre-crosslinking is performed by irradiation processing, the setting position and pre-crosslinking of different regions are controlled to ensure a good bonding effect between the connecting film and the battery sheet.
It effectively avoids the membrane material penetrates into the conductor and the fine grid lines during hot pressing, improves the connection reliability of the conductor and the fine grid lines, enhances the power generation efficiency of the photovoltaic module, and reduces the adhesion between the connecting film and equipment during hot pressing, and prevents separation.
Smart Images

Figure CN114864722B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaic technology, and in particular relates to a connecting film, a conductive composite and a photovoltaic component. Background Art
[0002] With the development of science and technology, energy problems are becoming increasingly serious. Photovoltaic technology, as a technology that can convert solar energy into electrical energy for people to use, can effectively utilize solar energy and make important contributions to solving energy problems.
[0003] Photovoltaic modules are the main application of photovoltaic technology, which can convert solar energy into electrical energy. However, the setting of the main grid in the module increases the cost of photovoltaic modules and reduces the power generation efficiency of photovoltaic modules. Therefore, the busbar-free technology has attracted people's attention. At present, the common implementation method of busbar-free photovoltaic modules is to embed the prepared conductor into the connection film, and then cover the connection film on the thin grid wire of the battery cell. During the hot pressing process, the conductor is solidified and welded to the thin grid wire through the surface low melting point metal.
[0004] The excessive fluidity of the connecting film in existing busbar-free photovoltaic modules can cause the connecting film material to penetrate into the conductor and the thin grid line, causing a cold weld, affecting the efficiency of the conductor in collecting electrons and reducing the power generation efficiency of the photovoltaic module. The use of a multi-layer film structure has high processing requirements, and stress is easily present between the film layers, resulting in film separation. Summary of the invention
[0005] The embodiment of the present application provides a connection film to solve the problem that the connection film material easily penetrates between the conductive part and the thin grid line of the battery cell, thereby ensuring a good bonding effect between the connection film and the battery cell.
[0006] One aspect of the present application provides a connecting film for a photovoltaic module, comprising:
[0007] a first region extending substantially along a first direction;
[0008] The second region substantially extends along the first direction, and the viscosity of the first region is lower than the viscosity of the second region.
[0009] Furthermore, m first regions and n second regions are arranged at intervals on the connection film, wherein m≥n, and n≥1; adjacent first regions are arranged substantially in parallel, and adjacent second regions are arranged substantially in parallel.
[0010] Furthermore, the width of the second region is greater than or equal to 0.2 mm and less than or equal to 10 mm.
[0011] Furthermore, the width of the second region is greater than or equal to 0.3 mm and less than or equal to 5 mm.
[0012] Furthermore, the pre-crosslinking degree of the first region is less than that of the second region, the pre-crosslinking degree of the first region is less than or equal to 15%, and the pre-crosslinking degree of the second region is greater than or equal to 30%.
[0013] Furthermore, the pre-crosslinking degree of the first region is less than or equal to 10%, and the pre-crosslinking degree of the second region is greater than or equal to 40%.
[0014] Furthermore, the viscosity of the first region is less than or equal to 10000 Pa·s, and the viscosity of the second region is greater than or equal to 5000 Pa·s and less than or equal to 200000 Pa·s.
[0015] Furthermore, the viscosity of the second region is greater than or equal to 5000 Pa·s and less than or equal to 150000 Pa·s.
[0016] Furthermore, the difference in viscosity between the second region and the first region is greater than or equal to 1000 Pa·s and less than or equal to 100000 Pa·s.
[0017] Furthermore, the connecting film is pre-crosslinked by irradiation treatment; preferably, the irradiation treatment includes at least one of electron beam irradiation or ultraviolet light irradiation.
[0018] The second aspect of the present application also provides a conductive composite for a photovoltaic module, comprising:
[0019] Connecting film, the connecting film comprising:
[0020] a first region extending substantially along a first direction;
[0021] A second region extending substantially along the first direction, wherein the pre-crosslinking degree of the second region is greater than the pre-crosslinking degree of the first region;
[0022] The conductive part is arranged on the surface of the second region in the connecting film and extends substantially along the first direction. The width of the conductive part is less than or equal to the width of the second region.
[0023] Furthermore, a difference between a width of the second region and a width of the conductive portion is greater than or equal to 0.1 mm and less than or equal to 30 mm.
[0024] Further, the width of the second region is greater than or equal to 0.2 mm and less than or equal to 10 mm, the pre-crosslinking degree of the first region is less than or equal to 15%, the pre-crosslinking degree of the second region is greater than or equal to 30%, the viscosity of the first region is less than or equal to 10000 Pa·s, the viscosity of the second region is greater than or equal to 5000 Pa·s and less than or equal to 200000 Pa·s, and the viscosity of the first region is less than the viscosity of the second region;
[0025] Furthermore, the width of the second region is greater than or equal to 0.3 mm and less than or equal to 5 mm, the pre-crosslinking degree of the first region is less than or equal to 10%, and the pre-crosslinking degree of the second region is greater than or equal to 40%.
[0026] A third aspect of the present application provides a photovoltaic module, which comprises a substrate, a packaging film, a battery string, a packaging film and a substrate in sequence.
[0027] The battery string includes,
[0028] The cells are arranged in an array;
[0029] The conductive composite is arranged on both sides of the battery cell, and the conductive composite includes:
[0030] A connecting film, the connecting film comprising:
[0031] a first region extending substantially along a first direction;
[0032] A second region extending substantially along the first direction, wherein the pre-crosslinking degree of the second region is greater than the pre-crosslinking degree of the first region;
[0033] The conductive part is at least partially arranged on the surface of the second area in the connecting film and extends basically along the first direction, and the width of the conductive part is less than or equal to the width of the second area; the conductive part connects adjacent battery cells together, one end of the conductive part is connected to the front side of one battery cell, and the other end is connected to the back side of another battery cell.
[0034] In summary, the embodiments of the present application have at least the following beneficial effects:
[0035] 1. The connection film provided in the embodiment of the present application solves the problem of poor solder joints caused by the film material easily penetrating between the conductive part and the fine grid lines of the battery cell during hot pressing by arranging a first region with a low pre-crosslinking degree and a second region with a high pre-crosslinking degree on the connection film, and arranging the conductive part on the surface of the second region, thereby making the connection between the conductive part and the fine grid lines more reliable;
[0036] 2. The connecting film provided in the embodiment of the present application is pre-cross-linked in different areas of the connecting film through irradiation treatment, and the setting position and pre-cross-linking degree of the first area and the second area are accurately controlled, ensuring that the setting position and viscosity of the first area and the second area can meet product requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic top view of a connecting film according to an embodiment of the present application;
[0038] Figure 2 In the embodiment of the present application, the connection film is Figure 1 Schematic diagram of the cross section in the AA direction;
[0039] Figure 3 A schematic top view of a conductive composite according to an embodiment of the present application;
[0040] Figure 4 For the conductive composite of the present application embodiment Figure 3 Schematic diagram of the cross section in the BB direction;
[0041] Figure 5 Another schematic diagram of a conductive composite according to an embodiment of the present application;
[0042] Figure 6 A schematic diagram of a photovoltaic assembly according to an embodiment of the present application;
[0043] Figure 7 A schematic diagram of a battery string according to an embodiment of the present application;
[0044] Figure 8 Another schematic diagram of a battery string according to an embodiment of the present application;
[0045] Photovoltaic module 100 , substrate 11 , encapsulation film 12 , battery string 13 , conductive composite 131 , connecting film 1311 , first region 1311 a , second region 1311 b , conductive portion 1312 , battery cell 132 , fine grid line 1321 . DETAILED DESCRIPTION
[0046] In order to make those skilled in the art better understand the scheme of the present invention, the technical scheme in the specific implementation mode of the present application will be clearly and completely described below in conjunction with the drawings in the implementation mode of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict. The present application will be described in detail below in conjunction with the embodiments.
[0047] At present, the common implementation method of busbar-free photovoltaic modules is to embed the prepared conductor into the connecting film to obtain a conductive composite, and then cover the conductive composite on the fine grid line of the battery cell. During the hot pressing process, the conductor is solidified and welded together with the fine grid line through the surface low melting point metal. The embodiment of the present application solves the problem that the existing connecting film has too much fluidity, and the film material is easy to penetrate between the conductive part and the fine grid line during the hot pressing process, thereby causing a cold weld. By controlling the pre-crosslinking degree at different positions of the connecting film, a first area with a low pre-crosslinking degree and a second area with a high pre-crosslinking degree are formed. At the same time, the conductive part is placed in the second area of the connecting film to ensure that the connection position between the connecting film and the conductive part has a low fluidity, effectively avoiding the film material from penetrating between the conductive part and the fine grid line of the battery cell during hot pressing, and improving the reliability of the electrical connection between the conductive part and the battery cell. The connecting film can play a key role in the busbar-free photovoltaic module. It fixes the conductive part and the battery cell together, and plays the role of carrying the conductive part to accurately position the battery cell and the conductive part. The connecting film prepared by using a low melting point and high fluidity film has excellent bonding performance, which can ensure the reliability of bonding between the connecting film and the battery cell. However, when the connection film with excessive fluidity is hot-pressed with the cell, the film material is easy to penetrate between the conductive part and the fine grid line of the cell due to its excessive fluidity, causing the conductive part to be poorly soldered, resulting in insulation between the conductive part and the fine grid line, reducing the ability of the conductive part to collect electrons, and thus reducing the power generation efficiency of the photovoltaic modules produced subsequently. Therefore, it is very necessary to develop a connection film that can not only meet high bonding performance but also ensure reliable electrical connection between the conductive part and the fine grid line.
[0048] The present application embodiment provides a connecting film 1311, such as Figure 1 and Figure 2 As shown, it includes a first area 1311a and a second area 1311b. The first area 1311a extends basically along the first direction, and the second area 1311b extends basically along the first direction, and the viscosity of the second area 1311b is greater than the viscosity of the first area 1311a. In the embodiment of the present application, the viscosity of the first area 1311a is relatively low, and has relatively high fluidity, which can ensure that the connecting film 1311 has good bonding and filling properties. The viscosity of the second area 1311b is relatively high, and the fluidity is relatively low, which can prevent the film material of the connecting film 1311 from penetrating into the conductive part 1312 and the fine grid line 1321 during the hot pressing process to cause the problem of cold soldering, and plays a good supporting role for the connecting film 1311. Providing a second region 1311b with greater viscosity can also reduce the bonding force between the connecting film 1311 and the hot pressing equipment during hot pressing, preventing the connecting film 1311 from adhering to the hot pressing equipment and being separated or partially separated from the battery cell 132, reducing the displacement of the conductive portion 1312 during hot pressing, and ensuring the reliability of the bonding between the battery cell 132 and the connecting film 1311 after hot pressing.
[0049] As a specific implementation method, Figure 1 and Figure 2As shown, the first area 1311a and the second area 1311b of the connecting film 1311 are alternately arranged. The connecting film 1311 is provided with m first areas 1311a and n second areas 1311b, where m≥n, and n≥1. The adjacent first areas 1311a are arranged substantially in parallel, and the adjacent second areas 1311b are arranged substantially in parallel. In the embodiment of the present application, the setting position of the second area 1311b of the connecting film 1311 corresponds to the setting position of the conductive part 1312, so as to ensure that the position of the conductive part 1312 is not offset during hot pressing. The number of the second areas 1311b corresponds to the number of the conductive parts 1312, and the second areas 1311b with a larger degree of pre-crosslinking can well support the conductive part 1312. Usually, the conductive parts 1312 are arranged substantially in parallel in the same direction, so the second areas 1311b are also arranged substantially in parallel in the same direction, so as to ensure that the conductive part 1312 is accurately positioned when the connecting film 1311 is subjected to hot pressing. In the embodiment of the present application, a first region 1311a with a lower pre-crosslinking degree is arranged between adjacent second regions 1311b to ensure the bonding performance of the connecting film 1311 and the battery cell 132, and to improve the reliability of the bonding between the connecting film 1311 and the battery cell 132. The first region 1311a and the second region 1311b are arranged at intervals to ensure the connection performance of the connecting film 1311. The arrangement of the first region 1311a can well bond the connecting film 1311 and the battery cell 132. In order to ensure the bonding effect, in the embodiment of the present application, the number of the first region 1311a cannot be less than the number of the second region 1311b, so as to ensure that the connecting film 1311 has excellent bonding performance.
[0050] As a specific embodiment, the width of the second region 1311b is greater than or equal to 0.2mm and less than or equal to 10mm. Preferably, the width of the second region 1311b is greater than or equal to 0.3mm and less than or equal to 5mm. In the embodiment of the present application, the second region 1311b on the connecting film 1311 needs to carry the conductive part 1312, so the width of the second region 1311b needs to be adapted to the width of the conductive part 1312. The width of the second region 1311b is appropriately adjusted according to the width of the conductive part 1312, so that the second region 1311b has sufficient width to carry the conductive part 1312, to prevent the conductive part 1312 from shifting to the first region 1311a during hot pressing, to avoid the conductive part 1312 from piercing the connecting film 1311 or reducing the electrical connection between the conductive part 1312 and the fine grid line 1321.
[0051] As a specific embodiment, the pre-crosslinking degree of the first region is less than that of the second region, the pre-crosslinking degree of the first region 1311a is less than or equal to 15%, and the pre-crosslinking degree of the second region 1311b is greater than or equal to 30%. Preferably, the pre-crosslinking degree of the first region 1311a is less than or equal to 10%, and the pre-crosslinking degree of the second region 1311b is greater than or equal to 40%. In the embodiment of the present application, the connecting film 1311 includes a first region 1311a with a smaller pre-crosslinking degree and a second region 1311b with a larger pre-crosslinking degree. The pre-crosslinking degree of the first region 1311a and the pre-crosslinking degree of the second region 1311b need to be subject to certain restrictions. The first region 1311a in the connecting film 1311 is the part that plays the main bonding role in the connecting film 1311, and its pre-crosslinking degree is relatively low. A lower pre-crosslinking degree can ensure that the first region 1311a has good fluidity and adhesion during hot pressing, and can ensure that the first region 1311a effectively fills the gap between the connecting film 1311 and the battery cell 132, reducing the risk of the connecting film 1311 detaching from the battery cell 132 after hot pressing, and enhancing the reliability of the connection between the connecting film 1311 and the battery cell 132. Therefore, the pre-crosslinking degree of the first region 1311a in the connecting film 1311 is less than or equal to 15%, preferably less than or equal to 10%. The second region 1311b in the connecting film 1311 plays the role of supporting the connecting film 1311, carrying the conductive part 1312, and preventing the conductive part 1312 from piercing the connecting film 1311 during hot pressing. The pre-crosslinking degree of the second region 1311b needs to be larger to ensure that the second region 1311b has sufficient strength to support the connecting film 1311 and prevent the conductive part 1312 from piercing the connecting film 1311. The second region 1311b with a larger pre-crosslinking degree has a higher strength, can play a good supporting role in the connecting film 1311, and can reduce the risk of the conductive part 1312 piercing the connecting film 1311 during hot pressing. The low fluidity brought by the high pre-crosslinking degree of the second region 1311b can also effectively prevent the film material from penetrating between the conductive part 1312 and the fine grid lines 1321, and improve the reliability of the connection between the conductive part 1312 and the fine grid lines 1321 of the battery cell 132. Therefore, the pre-crosslinking degree of the second region 1311b in the connecting film 1311 is greater than or equal to 30%, preferably greater than or equal to 40%.
[0052] As a specific embodiment, the viscosity of the first area 1311a of the connecting film 1311 in the embodiment of the present application is less than or equal to 10000Pa·s, and the viscosity of the second area 1311b is greater than or equal to 5000Pa·s and less than or equal to 200000Pa·s. Further, the viscosity of the second area 1311b is greater than or equal to 5000Pa·s and less than or equal to 150000Pa·s. The above viscosity can be measured according to the test method recorded in the standard ASTM D5289 and obtained at a frequency of 1Hz and a strain of 10%. The connecting film 1311 of the embodiment of the present application has a good bonding effect, the first area 1311a has good fluidity, and the second area 1311b has lower fluidity. The level of fluidity depends on the degree of pre-crosslinking, which is further reflected in the viscosity of the first area 1311a and the second area 1311b. Viscosity is a measure of fluid viscosity, a representation of the fluid flow force on its internal friction phenomenon, and can reflect the difficulty of fluid flow. The greater the viscosity, the more difficult the fluid is to flow. In the embodiment of the present application, the first region 1311a mainly provides adhesion and fills the gap between the connecting film 1311 and the battery cell 132. Therefore, the first region 1311a needs to have a relatively low viscosity to ensure that the first region 1311a can be better bonded and filled during hot pressing. The second region 1311b prevents the film material from penetrating between the conductive part 1312 and the thin grid line 1321, so it needs a relatively high viscosity and relatively low fluidity. The above viscosity is the viscosity in the temperature range of 120-150°C.
[0053] As a specific embodiment, the connecting film 1311 in the embodiment of the present application is pre-crosslinked by irradiation treatment. Preferably, the irradiation treatment includes at least one of electron beam irradiation or ultraviolet light irradiation. The connecting film 1311 provided in the embodiment of the present application needs to have a first region 1311a and a second region 1311b with different pre-crosslinking degrees, so a suitable pre-crosslinking treatment method is required to treat the connecting film 1311, so as to achieve the technical effect of alternating and spacing the first region 1311a and the second region 1311b in the connecting film 1311. Pre-crosslinking the connecting film 1311 by irradiation treatment can accurately set the first region 1311a and the second region 1311b with different pre-crosslinking degrees. During the irradiation treatment, the first area 1311a is appropriately shielded according to the technical requirements and actual production needs, so that the amount of radiation received by the first area 1311a is less than that of the second area 1311b, thereby achieving the technical effect of setting the first area 1311a and the second area 1311b with different pre-crosslinking degrees on the connecting film 1311. In the present application, a shielding material (such as a PET film or a metal foil, etc.) can be used to shield the irradiation on the first area 1311a, or a reagent that reduces the irradiation is printed on the first area 1311a on the connecting film 1311, and the first area 1311a and the second area 1311b with different pre-crosslinking degrees are set on the connecting film 1311. The shielding material used to shield the irradiation of the first area 1311a during the irradiation treatment can completely block the irradiation, or it can partially block the irradiation, so that the irradiation irradiated to the first area 1311a is weakened. The time that the first region 1311a is irradiated during the irradiation treatment can be controlled by controlling the shielding on the first region 1311a, and the pre-crosslinking degree between the first region 1311a and the second region 1311b can be effectively controlled by controlling the irradiation treatment time; the irradiation irradiated on the first region 1311a can also be controlled by controlling the degree of irradiation weakened by the shielding, so that the pre-crosslinking degree of the first region 1311a is less than that of the second region 1311b, and the pre-crosslinking degree between the first region 1311a and the second region 1311b can be effectively controlled by controlling the irradiation treatment time. The embodiment of the present application uses irradiation treatment to pre-crosslink the first region 1311a and the second region 1311b in the connecting film 1311, so that the first region 1311a and the second region 1311b can reach an ideal pre-crosslinking degree. The irradiation treatment includes at least one of electron beam irradiation or ultraviolet light irradiation. Electron beam irradiation is to irradiate the connection film 1311 with electron rays accelerated in a high-voltage electric field, and ionize and excite the molecules of various substances through the interaction between high-energy electrons and substances in the connection film 1311, thereby inducing chemical reactions to improve the performance of the connection film 1311. Electron beam irradiation processing of the connection film 1311 can prevent bacteria, extend the storage time, ensure product quality, improve mechanical properties, and enhance toughness.At the same time, electron beam irradiation also has the advantage of simple process. The amount of irradiation emitted by electron beam irradiation can be accurately controlled by computer, and the process of electron beam irradiation can be accurately controlled. The electron beam irradiation process has no environmental pollution, no chemical residue, and does not damage the appearance, quality and intrinsic characteristics of the connecting film 1311. No impurities will be introduced during the processing process, which can improve efficiency, without secondary pollution, and ensure the quality of the produced connecting film 1311. Ultraviolet irradiation is to add an appropriate amount of photocrosslinking agent to the film material of the connecting film 1311, and irradiate with ultraviolet light under certain conditions. The photocrosslinking agent absorbs ultraviolet light of a specific wavelength to generate free radicals, and the film material of the connecting film 1311 is cross-linked into a three-dimensional network structure through free radical reaction. The cost of ultraviolet irradiation is low and the pre-crosslinking speed is fast. After ultraviolet irradiation, the connecting film 1311 can be pre-crosslinked quickly, which can effectively reduce the production cost of the connecting film 1311.
[0054] As a specific embodiment, the raw material of the connecting film 1311 includes at least one of ethylene vinyl acetate copolymer, polyethylene acrylic acid, polyethylene methacrylic acid, polyolefin elastomer, thermoplastic polyolefin, thermoplastic polyurethane, polyvinyl butyral, low-density polyethylene or high-density polyethylene. In the embodiment of the present application, there are fewer restrictions on the raw materials of the connecting film 1311, and a variety of raw materials can be used for production, which can be appropriately adjusted according to specific production requirements. The connecting film 1311 includes a first area 1311a with a low pre-crosslinking degree and a second area 1311b with a high pre-crosslinking degree. The first area 1311a has high fluidity and good adhesion, and the second area 1311b has low fluidity and can carry the conductive part 1312. Therefore, the raw material of the connecting film 1311 in the embodiment of the present application needs to have excellent bonding performance and fluidity at a low pre-crosslinking degree to ensure that the connecting film 1311 has good bonding performance. When the pre-crosslinking degree is high, the raw material of the connecting film 1311 needs to have lower fluidity to prevent the film material of the connecting film 1311 from penetrating between the conductive part 1312 and the fine grid line 1321, and have a certain strength and adhesion to better support the conductive part 1312 and prevent the conductive part 1312 from shifting and piercing the connecting film 1311 during hot pressing.
[0055] The present application also provides a conductive composite 131 for a photovoltaic module, such as Figure 3 , Figure 4 and Figure 5 As shown, it includes a connecting film 1311 and a conductive part 1312. The connecting film 1311 includes a first region 1311a and a second region 1311b. In the connecting film 1311, the first region 1311a extends substantially along the first direction, and the second region 1311b extends substantially along the first direction. The pre-crosslinking degree of the second region 1311b is greater than the pre-crosslinking degree of the first region 1311a. The first region 1311a and the second region 1311b are alternately arranged and substantially parallel to each other. Figure 3 and Figure 4 As shown, the width of the conductive portion 1312 in the conductive composite 131 is less than or equal to the width of the second region 1311 b , and the conductive portion 1312 is disposed on the surface of the second region 1311 b and substantially extends along the first direction.
[0056] As a specific implementation, the difference between the width of the second region 1311b and the width of the conductive portion 1312 is greater than or equal to 0.1mm. In the embodiment of the present application, the setting of the second region 1311b needs to be appropriately adjusted according to the conductive portion 1312 to ensure that the conductive portion 1312 is on the second region 1311b. The width of the second region 1311b is set to be greater than the conductive portion 1312 to prevent the film material with better fluidity in the first region 1311a from penetrating between the conductive portion 1312 and the fine grid line 1321 during hot pressing. Therefore, the second region 1311b is at least 0.1mm wider than the conductive portion 1312 to ensure that the film material of the first region 1311a will not penetrate during hot pressing. At the same time, the difference between the width of the second region 1311b and the width of the conductive portion 1312 is greater than or equal to 0.1mm, which can also prevent the conductive portion 1312 from being offset due to the difference in fluidity between the first region 1311a and the second region 1311b during hot pressing, ensuring the accurate and reliable position of the conductive portion 1312 after hot pressing. The conductive part 1312 of the embodiment of the present application is arranged on the second area 1311b, and preferably, the conductive part 1312 is basically arranged in the middle of the second area 1311b. The conductive part 1312 is arranged in the middle of the second area 1311b so that the second area 1311b can better carry the conductive part 1312, reduce the probability of displacement of the conductive part 1312 during hot pressing, ensure reliable connection between the connecting film 1311 and the battery cell 132 after hot pressing, and ensure the accurate connection position between the conductive part 1312 and the fine grid line 1321.
[0057] As a specific embodiment, the width of the second region 1311b is greater than or equal to 0.2 mm and less than or equal to 10 mm. The pre-crosslinking degree of the first region 1311a is less than or equal to 15%, and the pre-crosslinking degree of the second region 1311b is greater than or equal to 30%. The viscosity of the first region 1311a is less than or equal to 10000 Pa·s, the viscosity of the second region 1311b is greater than or equal to 5000 Pa·s and less than or equal to 200000 Pa·s, and the viscosity of the first region 1311a is less than the viscosity of the second region. Preferably, the width of the second region 1311b is greater than or equal to 0.3 mm and less than or equal to 5 mm, the pre-crosslinking degree of the first region 1311a is less than or equal to 10%, and the pre-crosslinking degree of the second region 1311b is greater than or equal to 40%.
[0058] The present application also provides a photovoltaic assembly 100, such as Figure 6As shown, it includes a substrate 11, a packaging film 12, a battery string 13, a packaging film 12 and a substrate 11 in sequence. Figure 7 and Figure 8 As shown, the battery string 13 includes a conductive composite 131 and battery cells 132. In the battery string 13, the battery cells 132 are arranged in an array, and the conductive composite 131 is provided on both sides of the battery cells 132. The conductive composite 131 includes a connecting film 1311 and a conductive portion 1312. The connecting film 1311 includes a first region 1311a and a second region 1311b. In the connecting film 1311, the first region 1311a extends substantially along the first direction, and the second region 1311b extends substantially along the first direction. The pre-crosslinking degree of the second region 1311b is greater than the pre-crosslinking degree of the first region 1311a. The first region 1311a and the second region 1311b are alternately spaced and substantially parallel to each other. The width of the conductive portion 1312 is less than or equal to the width of the second region 1311b, and the conductive portion 1312 is provided on the surface of the second region 1311b and substantially extends along the first direction. As shown Figure 7 As shown, the conductive part 1312 is arranged in the second region 1311b of the connecting film 1311, which can effectively overcome the problem of unreliable connection between the conductive part 1312 and the fine grid line 1321 caused by the high fluidity of the connecting film 1311, and ensure that the film material of the connecting film 1311 does not enter between the conductive part 1312 and the fine grid line 1321 during hot pressing, thereby improving the reliability of the connection between the conductive part 1312 and the fine grid line 1321. When the connecting film 1311 is subjected to hot pressing, the second region 1311b can reduce the displacement of the conductive part 1312 caused by the fluidity of the connecting film 1311, thereby improving the reliability of the connection between the conductive part 1312 and the fine grid line 1321. Figure 8 As shown, the conductive portion 1312 connects adjacent battery cells 132 together, one end of the conductive portion 1312 is connected to the front side of one battery cell 132 , and the other end is connected to the back side of another battery cell 132 , thereby ensuring reliable electrical connection between the battery cells 132 .
[0059] In order to better illustrate the technical solution of the present application, the technical solution of the present invention will be further described below in conjunction with embodiments, but the present invention is not limited to the embodiments.
[0060] In the following examples and comparative examples, the adhesive film prepared by the same process is used as the base of the connecting film 1311, and then the first region 1311a and the second region 1311b are prepared by irradiation treatment to different degrees on the base. The base of the connecting film 1311 is a conventional EVA adhesive film, and its raw materials are 100 parts by weight of EVA resin, 0.5 parts by weight of cross-linking agent TAIC, 0.6 parts by weight of auxiliary cross-linking agent DCP, 0.2 parts by weight of coupling agent vinyl trimethoxy silane, 0.5 parts by weight of light stabilizer 770 and 0.2 parts by weight of antioxidant 1010. The base of the connecting film is prepared from the above raw materials by extrusion casting process.
[0061] Example 1
[0062] Preparation Figure 3 and 4 The connecting film 1311 shown, after the base is extruded and cast, is irradiated by a first irradiation device using an electron beam irradiation device with an energy of 150keV; then, it is irradiated by a second irradiation device using an electron beam irradiation device with an energy of 150keV to increase the irradiation dose, and during the irradiation treatment, a mask is used to cover only the first area 1311a, leaving the second area 1311b exposed; finally, the connecting film 1311 is obtained, and the mask corresponds to 9 hollow strip structures. The connecting film 1311 includes ten first areas 1311a and nine second areas 1311b. In the finally obtained connecting film 1311, the pre-crosslinking degree of the first area 1311a is 8%, the viscosity of the first area 1311a is 5000Pa·s, the pre-crosslinking degree of the second area 1311b is 45%, and the viscosity of the second area 1311b is 10000Pa·s; the width of the second area 1311b is 0.4mm.
[0063] Prepare the conductive composite 131, such as Figure 2 As shown, a tinned copper wire with a width of 0.1 mm is used as the conductive part 1312, and the conductive part 1312 is basically arranged parallel to the surface of the second area 1311b, and the conductive part 1312 is basically located in the middle position of the second area 1311b.
[0064] Example 2
[0065] The difference from Example 1 is that in Example 2: the pre-crosslinking degree of the first region 1311a is 45%, the viscosity of the first region 1311a is 10000 Pa·s, the pre-crosslinking degree of the second region 1311b is 50%, and the viscosity of the second region 1311b is 13000 Pa·s.
[0066] Example 3
[0067] The difference from Example 1 is that in Example 3: the pre-crosslinking degree of the first region 1311a is 0%, the viscosity of the first region 1311a is 1000 Pa·s, the pre-crosslinking degree of the second region 1311b is 8%, and the viscosity of the second region 1311b is 5000 Pa·s.
[0068] Example 4
[0069] The difference from Example 1 is that in Example 4: the pre-crosslinking degree of the first region 1311a is 0%, the viscosity of the first region 1311a is 1000 Pa·s, the pre-crosslinking degree of the second region 1311b is 70%, and the viscosity of the second region 1311b is 100000 Pa·s.
[0070] Example 5
[0071] The difference from Example 1 is that in Example 5: the width of the second region 1311b is 5 mm, and the width of the conductive portion 1312 is 0.5 mm.
[0072] Example 6
[0073] The difference from the first embodiment is that in the sixth embodiment: the width of the second region 1311 b is 10 mm, and the width of the conductive portion 1312 is 1 mm.
[0074] Example 7
[0075] The difference from Example 1 is that in Example 7: the pre-crosslinking degree of the first region 1311a is 0%, the viscosity of the first region 1311a is 1000 Pa·s, the pre-crosslinking degree of the second region 1311b is 70%, and the viscosity of the second region 1311b is 100000 Pa·s.
[0076] Example 8
[0077] The difference from Example 1 is that in Example 8: the pre-crosslinking degree of the first region 1311a is 3%, the viscosity of the first region 1311a is 2000 Pa·s, the pre-crosslinking degree of the second region 1311b is 5%, and the viscosity of the second region 1311b is 4000 Pa·s.
[0078] Example 9
[0079] The difference from Example 1 is that in Example 9: the pre-crosslinking degree of the first region 1311a is 13%, the viscosity of the first region 1311a is 5500 Pa·s, the pre-crosslinking degree of the second region 1311b is 15%, and the viscosity of the second region 1311b is 6000 Pa·s.
[0080] Example 10
[0081] The difference from Example 1 is that in Example 10: the pre-crosslinking degree of the first region 1311a is 0%, the viscosity of the first region 1311a is 1000 Pa·s, the pre-crosslinking degree of the second region 1311b is 72%, and the viscosity of the second region 1311b is 120000 Pa·s.
[0082] Embodiment 11
[0083] The difference from Example 1 is that in Example 11: the pre-crosslinking degree of the second region 1311b is 75%, the viscosity of the second region 1311b is 150000 Pa·s, the width of the second region 1311b is 13 mm, and the width of the conductive portion 1312 is 1 mm.
[0084] Example 12
[0085] The difference from Example 1 is that in Example 14: the connecting film 1311 includes nine first regions 1311a and nine second regions 1311b, and the width of the second region 1311b is 0.2 mm.
[0086] Comparative Example 1
[0087] The difference from Example 1 is that in Comparative Example 1, the viscosity of the first region and the second region of the connecting film 1311 are equal, both of which are 10000 Pa·s.
[0088] Comparative Example 2
[0089] The difference from Example 1 is that in Comparative Example 2, the width of the second region 1311 b is 0.1 mm, that is, the second region 1311 b and the conductive portion 1312 are of the same width.
[0090] Comparative Example 3
[0091] The difference from Example 1 is that in Example 12: the width of the second region 1311b is 0.2 mm, the conductive portion 1312 is substantially parallel to the surface of the first region 1311a, and the conductive portion 1312 is substantially located in the middle of the first region 1311a.
[0092] Comparative Example 4
[0093] The difference from Example 1 is that in Example 13: the width of the second region 1311b is 0.2 mm, and the conductive portion 1312 is substantially vertically disposed on the surfaces of the first region 1311a and the second region 1311b.
[0094] Performance effect test:
[0095] The conductive composites 131 in the above-mentioned embodiments 1-12 and comparative examples 1-4 are used to assemble the photovoltaic module 100 in the following manner.
[0096] The photovoltaic module 100 includes glass, EVA front layer packaging film 12, battery string 13, EVA rear layer packaging film 12, and back sheet from top to bottom. The lamination temperature is 145 degrees Celsius, the vacuum is drawn for 5 minutes, the lamination is performed for 10 minutes, and the pressure is 1 atmosphere. Figure 8 As shown, the battery string 13 includes a plurality of battery cells 132 and a conductive composite 131 disposed on both sides of the battery cells 132, specifically, two connecting films 1311 are separately disposed and connected by a conductive portion 1312, the conductive portion 1312 extends from the second area 1311b of the upper connecting film 1311 to the second area 1311b of the lower connecting film 1311, and the two connecting films 1311 are disposed opposite to each other.
[0097] Performance effect test method:
[0098] 1. Observe the EL image to determine whether there is a cold solder joint or a hidden crack. EL testing is a conventional technical means in the industry;
[0099] Cold solder joint: (quantitative expression)
[0100] ◎: No cold solder joints (none),
[0101] ○: 1-5 cold solder joints (few),
[0102] △: 5-10 cold solder joints (more),
[0103] ×: There are more than 10 cold solder joints (serious).
[0104] Hidden crack:
[0105] ◎: No hidden cracks,
[0106] ○: 1 to 3 hidden cracks,
[0107] △: 3 to 5 hidden cracks,
[0108] ×: There are more than 5 hidden cracks.
[0109] 2. Weather resistance: After the aging test, observe the EL image again to see if there are any new cold solder joints and hidden cracks;
[0110] Weathering resistance:
[0111] ◎: No new cold solder joints and hidden cracks (excellent),
[0112] ○: One new cold solder joint or hidden crack is added (good).
[0113] △: 2 to 3 new cold welds or hidden cracks (generally),
[0114] ×: There are more than 3 new cold solder joints or hidden cracks (poor).
[0115] 3. Bonding reliability: judge by observing whether there are bubbles or delamination;
[0116] bubble:
[0117] ◎: No bubbles or delamination,
[0118] ○: Bubbles or delamination 1-2 places,
[0119] △: 3 to 5 bubbles or delaminations,
[0120] ×: Bubbles or delaminations are more than 5.
[0121] Performance test results:
[0122] The performance test results are shown in Table 1 below.
[0123] Table 1 Performance test results of Examples 1-12 and Comparative Examples 1-4
[0124]
[0125]
[0126] The connection film provided in the embodiment of the present application has good bonding performance, and the conductive part is reliably connected to the fine grid line. It can be seen from the data in the table that the connection film in Examples 1-12 can effectively prevent cold solder joints and ensure that the conductive part is reliably connected to the fine grid line. There are few bubbles between the connection film and the battery cell after hot pressing in Examples 1-12, and the bonding reliability of the connection film is high. The connection film in Examples 1-12 has excellent weather resistance during hot pressing, which can provide good protection for the battery cell and increase its service life.
[0127] Since the viscosity of the connecting film in Comparative Example 1 is equal to that of the first region and the second region, it cannot take into account the performance requirements of high bonding performance in the first region and low fluidity in the second region, and it produces more obvious bubbles and delamination, and its weather resistance is also poor. In the conductive composite in Comparative Example 2, since the width of the second region is the same as that of the conductor, the conductor cannot be well protected after hot pressing, so that the resin in the first region penetrates between the conductor and the grid line, resulting in more serious cold solder joints. In Comparative Example 3, the conductive part is arranged in the first region, and the viscosity of the first region is relatively small and the fluidity is relatively poor. During hot pressing, the resin in the first region penetrates between the conductor and the grid line, resulting in more serious cold solder joints. In Comparative Example 4, the conductive part is arranged perpendicular to the first region and the second region, and both cold solder joints and hidden cracks are more serious.
[0128] In summary, the connection film provided in the embodiment of the present application has good bonding performance, the conductive part is reliably connected to the fine grid line, the raw material sources are multiple, the cost is low, and it has good application prospects.
[0129] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the claims attached to this application.
Claims
1. A connection film for a photovoltaic module, used to connect a conductive part to the surface of a photovoltaic cell, characterized in that: include: A first region, the first region is used to bond the connecting film to the surface of the photovoltaic cell sheet, and the first region substantially extends along a first direction; a second region, the second region is used to carry the conductive portion, the width of the second region is greater than the width of the conductive portion, the second region substantially extends along the first direction, the viscosity of the second region is greater than the viscosity of the first region, and the width of the second region is greater than or equal to 0.2 mm and less than or equal to 10 mm; The viscosity of the first region is less than or equal to 10000 Pa·s, the viscosity of the second region is greater than or equal to 5000 Pa·s and less than or equal to 150000 Pa·s, and the difference between the viscosity of the second region and the first region is greater than or equal to 1000 Pa·s and less than or equal to 100000 Pa·s.
2. A connecting film according to claim 1, characterized in that: The connecting film is provided with m first regions and n second regions at intervals, wherein m≥n, and n≥1; adjacent first regions are arranged substantially in parallel, and adjacent second regions are arranged substantially in parallel.
3. A connecting film according to claim 1, characterized in that: The width of the second region is greater than or equal to 0.3 mm and less than or equal to 5 mm.
4. A connecting film according to claim 1, characterized in that: The pre-crosslinking degree of the first region is less than that of the second region, the pre-crosslinking degree of the first region is less than or equal to 15%, and the pre-crosslinking degree of the second region is greater than or equal to 30%.
5. A connecting film according to claim 1, characterized in that: The pre-crosslinking degree of the first region is less than or equal to 10%, and the pre-crosslinking degree of the second region is greater than or equal to 40%.
6. A connecting film according to claim 1, characterized in that: The connecting film is pre-crosslinked by irradiation treatment.
7. A connecting film according to claim 6, characterized in that: The irradiation treatment includes at least one of electron beam irradiation or ultraviolet light irradiation.
8. A conductive composite for photovoltaic modules, characterized in that: include: According to any one of claims 1 to 7, the connecting film and the conductive portion are provided on the surface of the second region of the connecting film and extend substantially along the first direction.
9. The conductive composite for photovoltaic modules according to claim 8, characterized in that: A difference between a width of the second region and a width of the conductive portion is greater than or equal to 0.1 mm and less than or equal to 30 mm.
10. The conductive composite for photovoltaic modules according to claim 8, characterized in that: The pre-crosslinking degree of the first region is less than or equal to 15%, and the pre-crosslinking degree of the second region is greater than or equal to 30%.
11. The conductive composite for photovoltaic modules according to claim 8, characterized in that: The width of the second region is greater than or equal to 0.3 mm and less than or equal to 5 mm.
12. A photovoltaic module, which comprises a substrate, a packaging film, a battery string, a packaging film and a substrate in sequence, characterized in that: The battery string comprises a battery cell, a connecting film as claimed in any one of claims 1 to 7, and a conductive portion disposed in the second region of the connecting film; Alternatively, the cell string comprises the conductive composite for a photovoltaic module according to any one of claims 8 to 11; The conductive part connects the adjacent battery cells together, one end of the conductive part is connected to the front side of one battery cell, and the other end is connected to the back side of another battery cell.
Citation Information
Patent Citations
Photovoltaic packaging adhesive film, photovoltaic module and preparation method of photovoltaic module
CN112289879A
Monocell, packaging film, solar cell module and manufacturing method thereof
CN113035986A
Connecting film for photovoltaic battery piece
CN113707744A
Connecting member
JP1992301382A
Polymer conductor sheets, solar cells and methods for producing same
US20180315875A1